STUDENTS’ PERCEPTIONS OF FINAL REPORT ADVISORY SERVICES IN ENGLISH DEPARTMENT OF STATE POLYTECHNIC OF SRIWIJAYA - Moehamad Ridhwan; Zakaria Zakaria; Eriza Eriza; Munaja Rahma (HOLISTICS, 2018)
This study was aimed at finding out the students’ perceptions of final report advisory services in English Department of State polytechnic of Sriwijaya. This would expectedly give insights on how well the tasks of providing services in terms of assisting students with their final report writing had been performed. Questionnaires were self-made, and therefore the validity and reliability test were conducted in which 19 students were involved. The results of this piloting project were analyzed by using the Pearson Product Moment Coefficient. To get the data, 77 students were requested to fill out the questionnaires. Through the use of statistic desriptive analysis, the data were processed and then described in words and numbers. The conclusion was that the lecturers of The English Department had performed their task porperly in providing final report advisory services to their students.